URGENSI DITERBITKANNYA INSTRUKSI MENTERI DALAM NEGERI DAN SEJUMLAH PERATURAN LAINNYA DI DAERAH TERKAIT DENGAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) - Elwidarifa Marwenny; Helfira Citra; Sry Wahyuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Regulation of Government No. 21 of 2020 confirms in the consideration that the Large-Scale Social Restriction (PSBB) policy is set taking into account the spread of Covid-19 with the number of cases and/or the number of deaths increasing and spreading across regions and across countries. After the policy related to PSBB, the government again issued a Ministerial Instruction concerning the Enforcement of Restrictions on Community Activities (PPKM) which was issued four times and not only that in a number of regions, PPKM policies were also implemented based on various regional policies in the form of circulars. Thus, the question arises: What is the urgency of the issuance of the Instruction of the Minister of Home Affairs and a number of other regulations related to the Enforcement of Restrictions on Community Activities (PPKM) and what are the legal implications of the issuance of the Instruction of the Minister of Home Affairs and a number of other regulations related to the Enforcement of Restrictions on Community Activities (PPKM). To answer this question, the author uses a normative juridical approach by reviewing a number of related regulations and a number of literatures so that it can be concluded that the instructions of the Minister of Home Affairs and a number of other regulations related to the Enforcement of Restrictions on Community Activities (PPKM) are fully arrenged under the authority of the government. The government can assess whether a policy regulation needs to be issued or not especially related to the condition of the country in a disaster situation and the issuance of instructions from the minister of home affairs and a number of other regulations related to the Implementation of Restrictions on Community Activities (PPKM) does not violate the provisions of any law as long as it is carried out not outside the authority of the governments which has the authority and the implication is only an appeal for the community to comply with its implementationKeywords: Instruction of Minister, PPKM, regulation